2022
DOI: 10.1186/s12877-022-03620-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a behavioural framework for dementia care partners’ fall risk management

Abstract: Background Although older adults living with dementia (OLWD) are at high risk for falls, few strategies that effectively reduce falls among OLWD have been identified. Dementia care partners (hereinafter referred to as “care partners”) may have a critical role in fall risk management (FRM). However, little is known about the ways care partners behave that may be relevant to FRM and how to effectively engage them in FRM. Methods Semi-structured, in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Tandem standing is a test of postural stability, particularly in the lateral direction [26], which is considered an important factor in predicting falls [27,28]. The dependent group in this study included patients who required supervision while walking, and the degree of fall risk is largely related to whether they required supervision [29][30][31]. This reinforces the finding that tandem standing is suitable for determining whether a patient should be supervised.…”
Section: Discussionsupporting
confidence: 63%
“…Tandem standing is a test of postural stability, particularly in the lateral direction [26], which is considered an important factor in predicting falls [27,28]. The dependent group in this study included patients who required supervision while walking, and the degree of fall risk is largely related to whether they required supervision [29][30][31]. This reinforces the finding that tandem standing is suitable for determining whether a patient should be supervised.…”
Section: Discussionsupporting
confidence: 63%
“…However, literature suggested that Black older people in the United States were at a higher risk of experiencing CI ( 66 ) and were more likely to report risk factors associated with falling, such as physical limitations ( 67 ). The lower prevalence of fall worry among older Blacks may reflect their more extensive care networks compared to non-Hispanic Whites ( 68 ) and greater collaborations within care networks ( 69 ) given the importance of informal care partners in reducing fall worry for older people with CI ( 70 ). It may also reflect resilience as a culturally valued trait that has historically helped African American communities deal with oppression and discrimination ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual impairment causes a wide range of challenges to older people’s physical function and psychological health, which are all associated with increased fall worry ( 77 ). However, visual impairment may also enable older people and their care partners to develop adaptive strategies to mitigate the negative impact of fall worry on their daily activities ( 78 ), even before the onset of CI ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management following a fall incurs a high cost and is an issue for policymakers, healthcare providers and many personnel involved in looking after older adults with dementia, including family members [6,7]. For a person with dementia, there are numerous multi-factorial, intrinsic and extrinsic fall risk factors [8], such as lighting, environmental hazards, co-morbidities and polypharmacy, as well as cognitive impairment [9].…”
Section: Introductionmentioning
confidence: 99%